PERAN KETERAMPILAN KOMUNIKASI SEBAGAI SOFT SKILLS DALAM PENYELESAIAN KONFLIK AKADEMIK: PERSEPSI MAHASISWA GENERASI Z - Hanifah, Dhiya Aulia; Muhithoh, Tety; Akbar, Muhammad Yusuf; Ismail, Dingot Hamonangan (POLITEKNIK LP3I JAKARTA, 2026)
Academic conflict is a phenomenon that is inseparable from the dynamics of student life, especially in Generation Z who have strong digital communication characteristics. This study aims to analyze the characteristics of academic conflicts experienced by Generation Z students, their perception of the role of communication skills as soft skills in conflict resolution, and communication factors that affect the success and failure of academic conflict resolution. This study uses a descriptive quantitative approach by involving 100 active students as respondents. Data were collected through questionnaires and analyzed descriptively. The results of the study show that academic conflicts among Generation Z students are generally interpersonal and task conflicts, with low to moderate intensity and arise situationally. The dominant conflict resolution strategy is direct and collaborative communication, although some students still choose to avoid conflict. The majority of respondents view communication skills as a factor that greatly influences the success of conflict resolution, especially open and honest communication, focus on solutions, active listening, empathy, and emotional management. On the other hand, communication failures are most caused by uncontrolled emotions, ego and defensiveness, and an unwillingness to accept input. These findings affirm the importance of strengthening communication skills and conflict resolution as part of the development of students' soft skills in higher education.